Case Report: Clinical, laboratory, and pathological findings in cows with osteomyelitis of the ribs and sternum and endocarditis valvularis thromboticans - Rachidi, Fanny; Elhadi, Abass; Bittner-Schwerda, Lilli; Schären-Bannert, Melanie; Köller, Gábor; Schinköthe, Jan; Majcher, Anna; Diehl, Benjamin; Hansmann, Florian; Kühn, Tilman; Starke, Alexander (Frontiers in Veterinary Science, 2025)
The etiological relationship between osteomyelitis (OM) of the ribs and sternum and endocarditis valvularis thromboticans (EVT) in dairy cattle was assessed using clinical, ultrasonographic, bacteriologic, and postmortem findings. Five dairy cows (2nd–6th lactation, 135–304 days in milk, 490–630 kg) were admitted to our clinic because of low production and poor body condition. Clinical examination revealed abnormalities in the circulatory and locomotor system, as well as the ribs and sternum. Ultrasonographic examinations of the heart, ribs, and sternum were performed, and samples were collected for laboratory analyses. The cows underwent an orthopedic examination and bacteriologic testing of blood (N = 5), abscesses of the ribs or sternum (N = 3), and synovial fluid (N = 2). All five cows were euthanized because of a poor prognosis, and a postmortem examination was carried out. During the postmortem examination, samples were collected from endocardial lesions (N = 4) and abscesses of the ribs and/or sternum (N = 2) that had not been accessible intra vitam. The physical condition of the cows suggested a chronic metastatic disease accompanied by pyemia. All cows had OM of the ribs or sternum and EVT, along with other inflammatory diseases, including arthritis (N = 4), tendovaginitis (N = 2), and abscesses (N = 2). These clinical diagnoses were confirmed during the postmortem examination. Bacteriologic examination revealed Trueperella pyogenes in the rib and sternal lesions (N = 5), blood cultures (N = 3), endocardial lesions (N = 3), and samples taken from the uterus, kidney, spleen, and muscle (N = 4). Our results emphasize the importance of ruling out EVT in cattle with lesions of the ribs and sternum. Ultrasonographic and microbiologic examinations support the diagnosis and help determine the extent and severity of the changes. While a definitive primary cause cannot be identified due to the animals’ polymorbid condition, the observed lesions suggest that apostematous inflammation of the ribs or sternum may act as a potential source of infection.